TUJUAN NEGARA DALAM ISLAM MENURUT YUSUF AL-QARADHAWI - Sigit Ridwan Abdullah (Asy-Syari'ah, 2017)
AbstractYusuf al-Qaradawi is one of the figures of so many scholars who contributed to the thinking of the Islamic state. His attention to politics and state is evidenced by the   presence of some of his works such as الإسلام في الدولة فقه من (Fiqh of State in Islamic Perspective),  الشرعية السياسة (Political Sharia), الإسلام مواجهة في العلماني التطرف (Extreme Secular Attitudes towards Islam), وهم لا حقيقة اللإسلامية اللأمة (The Political Unit of Ummah is a Reality). This research tried to review Yusuf al-Qaradawi's view on Islamic state, using descriptive analytical methods and literature review upon the above stated Yusuf al-Qaradawi's books or writings. The research result shows that Islamic state according to Yusuf al-Qaradawi is "a state based on faith and thought." He stated that there are four objectives of Islamic government. Firstly, Islamic Government does not aim to control the nation and its natural resources, but to preserve and protect the people. Secondly, fulfill the mandate from the owner. Thirdly, uphold justice for the human race. Fourthly, strengthen the religion in the earth as the most important goal by establishing faith, hudud and applying the law and its messages.Keywords: Islamic State, State aims, Yusuf al-QaradhawiAbstrakYusuf al-Qaradhawi merupakan salah satu tokoh dari begitu banyak tokoh pemikir yang turut memberikan kontribusi pemikiran tentang negara Islam. Perhatiannya terhadap politik dan kenegaraan terbukti dengan adanya beberapa karya beliau seperti bukuمن فقه الدولة في الإسلام (Fiqih Negara dalam Perspektif Islam), السياسة الشرعية  (Politik Syariah), التطرف العلماني في مواجهة الإسلام (Sikap Sekuler Ekstrim dalam Menghadapi Islam), اللأمة اللإسلامية حقيقة لا وهم (Kesatuan Politik Ummat Islam adalah Suatu Kenyataan). Penelitian ini menganalisis pandangan Yusuf al-Qaradhawi terhadap negara Islam dengan menggunakan metode deskriptif analitis dalam bentuk library research, terhadap buku-buku atau tulisan lepas Yusuf al-Qaradhawi tersebut di atas. Negara Islam menurut Yusuf al-Qaradhawi adalah “negara yang berlandaskan akidah dan pemikiran.” Ia menyatakan bahwa ada empat tujuan pemerintahan Islam yaitu: Pertama, Pemerintahan Islam tidak bertujuan untuk menguasai lahir batin, tetapi untuk memelihara dan melindungi rakyat. Kedua, menunaikan amanat kepada pemiliknya. Ketiga, menegakan keadilan bagi ummat manusia. Keempat, mengokohkan agama di muka bumi sebagai tujuan yang paling utama dengan menanamkan akidah, hudud dan mengaplikasikan hukum dan pesan-pesannya.Kata kunci: Negara Islam, tujuan negara, Yusuf al-Qaradhawi